On the p-Version of the Schwab-Borchardt Mean II - Edward Neuman (International Journal of Mathematics and Mathematical Sciences)
This paper deals with the p-version of the Schwab-Borchardt mean. Lower and upper bounds for this mean, expressed in terms of the weighted geometric and arithmetic means of its variables, are obtained. Applications to four bivariate means, introduced earlier by the author of this paper, are included.